Influence of the RpoS (KatF) sigma factor on maintenance of viability and culturability of Escherichia coli and Salmonella typhimurium in seawater. - Munro, P M (1995)
The sigma factor RpoS is essential for stationary-phase-specific, multiple-stress resistance. We compared the viabilities (direct viable counts) and culturabilities (colony counts) in seawater of Escherichia coli and Salmonella typhimurium strains and those in which rpoS was deleted or which were deficient in guanosine 3',5'-bispyrophosphate (ppGpp) synthesis (relA spoT). RpoS, possibly via ppGpp regulation, positively influenced the culturability of these bacteria in oligotrophic seawater. This influence closely depended, however, upon the growth state of the cells and the conditions under which they were grown prior to their transfer to seawater. The protective effect of RpoS was observed only in stationary-phase cells grown at low osmolarity. A previous exposure of cells to high osmolarity (0.5 M NaCl) also had a strong influence on the effect of RpoS on cell culturability in seawater. Both E. coli and S. typhimurium RpoS mutants lost the ability to acquire a high resistance to seawater, as observed in both logarithmic-phase and stationary-phase RpoS+ cells grown at high osmolarity. A previous growth of S. typhimurium cells under anoxic conditions also modulated the incidence of RpoS on their culturability. When grown anaerobically at high osmolarity, logarithmic-phase S. typhimurium RpoS+ cells partly lost their resistance to seawater through preadaptation to high osmolarity. When grown anaerobically at high osmolarity until stationary phase, both RpoS+ and RpoS- cells retained very high levels of both viability and culturability and then did not enter the viable but nonculturable state for over 8 days in seawater because of an RpoS-independent, unknown mechanism.